Transcriptomic Analysis Revealed an Important Role of Peroxisome-Proliferator-Activated Receptor Alpha Signaling in Src Homology Region 2 Domain-Containing Phosphatase-1 Insufficiency Leading to the Development of Renal Ischemia-Reperfusion Injury - Yan, Sijia; Sui, Mingxing; Tian, Hongzhe; Fu, Jiazhao; Li, Yanfeng; Chen, Jing; Zeng, Li; Ding, Xianting (Frontiers in Medicine, 2022)
In kidney transplantation, the donor kidney inevitably undergoes ischemia-reperfusion injury. It is of great importance to study the pathogenesis of ischemia-reperfusion injury and find effective measures to attenuate acute injury of renal tubules after ischemia-reperfusion. Our previous study found that SHP-1 insufficiency aggravates renal ischemia-reperfusion injury. In this study, we systematically analyzed differences in the expression profiles of SHP-1 (encoded by Ptpn6)-insufficient mice and wild-type mice by RNA-seq. We found that a total of 161 genes showed at least a two-fold change, with a false discovery rate < 0.05 in Ptpn6 +/mev mice after ischemia-reperfusion injury and 42 genes showing more than a four-fold change. Of the eight genes encoding proteins with immunoreceptor tyrosine-based inhibitory motifs that bind to Ptpn6, three were upregulated, and five were downregulated. We found that for the differentially expressed genes with a fold change > 2, the most significantly enriched KEGG pathways were the cell division pathway and peroxisome-proliferator activated receptor PPARα signaling pathways. Furthermore, the downregulated genes of the PPARα signaling pathway were mainly related to fatty acid absorption and degradation. Using an agonist of the PPARα signaling pathway, fenofibrate, we found that renal ischemia-reperfusion injury was significantly attenuated in Ptpn6 +/mev mice. In summary, our results show that insufficiency of SHP-1 inhibits the expression of genes in the PPARα signaling pathway, thereby leading to increased ROS and exacerbating the renal ischemia-reperfusion injury. The PPARα signaling agonist fenofibrate partially attenuates renal ischemia-reperfusion injury induced by SHP-1 insufficiency.